Sympatric threatened Iberian leuciscids exhibit differences in Aeromonas diversity and skin lesions’ prevalence - Grilo, Miguel (2021)
Assessments regarding health aspects of Iberian leuciscids are limited. There is currently an information gap regarding effects of infectious diseases on these populations and their role as a possible conservation threat. Moreover, differences in susceptibility to particular agents, such as Aeromonas spp., by different species/populations is not clear. To understand potential differences in Aeromonas diversity and load, as well as in the prevalence and proportion of skin lesions, in fishes exposed to similar environmental conditions, an observational study was implemented. Using a set of 12 individuals belonging to two sympatric Iberian leuciscid species (Squalius pyrenaicus and Iberochondrostoma lusitanicum), the skin lesion score in each individual was analyzed. Furthermore, a bacterial collection of Aeromonas spp. isolated from each individual was created and isolates’ load was quantified by plate counting, identified at species level using a multiplex-PCR assay and virulence profiles established using classical phenotypic methods. The similarity relationships of the isolates were evaluated using a RAPD analysis. The skin lesion score was significantly higher in S. pyrenaicus, while the Aeromonas spp. load did not differ between species. When analyzing Aeromonas species diversity between fishes, different patterns were observed. A predominance of A. hydrophila was detected in S. pyrenaicus individuals, while I. lusitanicum individuals displayed a more diverse structure. Similarly, the virulence index of isolates from S. pyrenaicus was higher, mostly due to the isolated Aeromonas species. Genomic typing clustered the isolates mainly by fish species and skin lesion score. Specific Aeromonas clusters were associated with higher virulence indexes. Current results suggest potential differences in susceptibility to Aeromonas spp. at the fish species/individual level, and constitute important knowledge for proper wildlife management through the signalization of at-risk fish populations and hierarchization of conservation measures.